Implementasi Pasal 21 Ayat (2) Huruf A Undang-Undang Nomor 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya di Bali - I Nyoman Alit Suardana; I Nyoman Budiana (UNES Law Review, 2023)
The problem in this research is why the implementation of Article 21 paragraph (2) letter a of law number 5 of 1990 has not been optimally implemented regarding living natural resources and their ecosystems in Susut District, Bangli Regency. The purpose of this study was to obtain data and analyze the factors causing the non-optimal implementation of Article 21 paragraph (2) letter a of Law Number 5 of 1990 in the case of eagle rearing by residents in Susut District, Bangli Regency, to find out and analyze the efforts made by the government. in optimizing the implementation of these regulations. The method used is descriptive with the type of normative legal research that is descriptive analysis. The technique of collecting legal materials is by studying literature, rules and literature related to the title of the study, and using a descriptive argumentative approach. The analysis uses descriptive with the theory of legal effectiveness. The results of the study indicate that the implementation of Article 21 Paragraph (2) Letter a of Law Number 5 of 1990 has not been maximized. It was found that there are still residents who keep eagles, this is caused by several factors including weak law enforcement, limited personnel on duty in the field, lack of funds provided by the government, lack of legal awareness among the community. Meanwhile, efforts that have been made by the government include conducting education and training for personnel capacity, conducting socialization of laws, conducting monitoring and investigations, managing, utilizing and preserving conservation areas, collaborating with other institutions/agencies in conservation efforts of living natural resources and their ecosystems. Efforts will be made by the government is to form a non-governmental group.